Laying Diet Supplementation with Ricinus communis L. leaves and Evaluation of Productive Performance and Potential Modulation of Antioxidative Status - Bing-Wen Su; Wei-Chih Lin; Li-Jen Lin; Chung-Ming Huang; Wen-Yang Chuang; Den-Jen Wu; Chia-Hung Shih; Tzu-Tai Lee (The Journal of Poultry Science, 2020)
This study evaluated the antioxidant capacity of Ricinus communis L. (RC) leaves and powder when used as a feed additive for laying hens. Results showed that the total phenolic content of the aqueous leaf extract of Ricinus communis L. (RCE) was 48.39 mg gallic acid equivalent (GAE) per gram dry weight (DW). The flavonoid content was 9.76 mg quercetin dihydrate equivalent (QE)/g DW. Ferrous chelating activity was approximately 56.2% with an RCE concentration of 1 mg/mL; the highest chelating activity was 91.2% with 4 mg/mL extract. The reducing power of 1 mg/mL RC was 1.17 times better than 1 mg/mL butylated hydroxytoluene (BHT). The Trolox equivalent antioxidant capacity (TEAC) value of 12.5 mg/mL RCE was equivalent to 3.09 mg/mL Trolox. RCE (10 mg/mL) had a lipid oxidative inhibition capacity of 35.3%. A total of 80 ISA brown laying hens at twenty-nine weeks of age were randomly allocated into the control or 1 of 3 treatment groups; the latter received 0.5%, 1% or 2% of RC, respectively, for 12 weeks. Results showed that the RC supplementation improved the feed conversion rate and 0.5% RC generated the best results. Additionally, the egg yolk score was significantly increased in all RC-supplemented groups. Moreover, there was no significant difference in serum characteristics between the treatment groups. Serum antioxidant enzyme activity showed that superoxide dismutase (SOD) activity increased in the RC-supplemented groups relative to the control but was not significantly different. mRNA expression levels of the antioxidant regulatory genes GCLC, GST, HO-1, SOD1, and SOD2 were significantly increased with 2% RC supplementation. In summary, RC is a suitable feed additive for laying hens and the addition of 0.5% RC leaf powder resulted in the greatest benefits.